The relationship between stroke metrics, work rate and performance in slalom kayakers - Macdermid, P. W.; Olazabal, T. (Biomechanics, 2022)
The purpose of this study was to assess the relationship between work rate, stroke metrics, and performance in whitewater slalom. Twelve Spanish, nationally competitive whitewater slalom kayakers took part in a simulated competition while using an instrumented kayak paddle to record stroke metrics over a simulated race, total duration and sectional splits. Performance time was highly correlated to overall power output (r2 = 0.511, p < 0.001), where kayakers demonstrated a positive pacing strategy with power output significantly decreasing over successive sectional splits (158 ± 40, 112 ± 32 and 65 ± 33 W, p < 0.001). This resulted in an increased stroke duration (p < 0.001), time to peak force (p < 0.001), a decrease in stroke peak force (p < 0.001), and rate of peak force development (p < 0.001) over elapsed time. As such, work rate is deemed an objective metric to monitor performance, prescribe training, and ascertain optimal pacing strategies in canoe slalom.